Graphene-coated lithium iron phosphate positive electrode material and preparation method thereof

By coating the lithium iron phosphate positive electrode material with graphene, the mixed preparation method of small particle size FePO4/GO, large particle size FePO4/GO and FePO4/SWCNT was solved, and the high impedance and polarization problems of lithium iron phosphate materials during the charge and discharge process was significantly improved, and the compaction density and electrochemical performance of the material were improved, and the energy density and magnification capacity of the battery were improved.

CN119841298AActive Publication Date: 2025-04-18HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510307532.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-18
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

LiFePO4 material has high impedance and polarization problems during charging and discharging, resulting in poor actual specific capacity and magnification capabilities. At the same time, its low electron and ionic conductivity limits the energy density of the battery.

Method used

The compaction density and electrochemical properties of the material are improved by graphene-coated lithium iron phosphate positive electrode material, and the mixed preparation method of small-particle FePO4/GO, large-particle FePO4/GO and FePO4/SWCNT are used. The method includes spray drying of the mixture, pre-calcining, dopamine oxidation and autopolymerization and calcining, etc., to form a double-layer coated porous carbon material.

Benefits of technology

It significantly improves the compaction density and electrochemical properties of the positive electrode material, improves the conductivity and cyclic stability of the material, and enhances the energy density and magnification capabilities of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a graphene-coated lithium iron phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of lithium iron phosphate positive electrode materials.The preparation method comprises the steps that firstly, iron phosphate is loaded on graphene, the time is adjusted by controlling the pH value, small-particle-size FePO4 / GO and large-particle-size FePO4 / GO are accurately obtained, FePO4 / SWCNT is prepared by loading iron phosphate on a single-walled carbon nanotube, and then the graphene-coated lithium iron phosphate positive electrode material is obtained; the preparation method comprises the following steps: carrying out a pre-calcination reaction on a loaded material and a lithium source to form graphene-coated lithium iron phosphate, carrying out dopamine oxidation self-polymerization to form polydopamine, coating the outer layer of the graphene-coated lithium iron phosphate with the polydopamine, and carrying out calcination carbonization to form double-layer coating of a porous carbon material and graphene. The particle size distribution of the prepared positive electrode material is optimized by utilizing the iron phosphate loaded materials with different particle sizes and shapes, the compaction density is improved, the conductivity is improved by utilizing graphene coating, and the positive electrode material is endowed with excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium iron phosphate positive electrode materials, and in particular relates to a graphene-coated lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate LiFePO4 (LFP) has a place in the cathode material market with its high theoretical capacity, high safety performance and high structural stability. However, the inherent low electronic conductivity (10 -9 Up to 10 -8 S cm -1 ) and low ionic conductivity (10 -11 Up to 10 -9 S cm -1 ) will cause high impedance and polarization problems during the charge and discharge process, as well as the subsequent problems of poor actual specific capacity and rate capability. Therefore, it is necessary to improve the kinetic properties of LiFePO4 materials to increase the capacity of the materials at different charge and discharge rates.

[0003] Secondly, in order to meet the market demand for higher energy density of lithium-ion batteries, the energy density of the battery needs to be increased while keeping the volume unchanged. The compaction density of the LiFePO4 positive electrode needs to be increased. The compaction density of the LiFePO4 electrode in most existing commercial batteries is 2.4-2.5g / cm 3 , the compaction density needs to be further improved so that the energy density of the battery can meet higher requirements. Summary of the invention

[0004] The object of the present invention is to provide a graphene-coated lithium iron phosphate positive electrode material and a preparation method thereof, so as to improve the compaction density and electrochemical performance of the positive electrode material.

[0005] The purpose of the present invention can be achieved through the following technical solutions: The present invention provides a method for preparing a graphene-coated lithium iron phosphate positive electrode material, comprising the following steps: Step 1, mixing small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT in a mass ratio of (3-5): (1-2): (0.5-1) to form a mixture; Step 2: adding lithium source and water to the mixture to form a suspension, spray drying to obtain a solid material, and pre-calcining at 700-750° C. for 6-8 hours under a nitrogen atmosphere to form a precursor; Step 3: Disperse the precursor in water at a mass concentration of 1-3 g / L, add dopamine hydrochloride and ammonia water, react at 30-40° C. for 6-8 hours, filter and vacuum dry, and calcine at 700-750° C. for 2-4 hours in a nitrogen atmosphere to obtain the positive electrode material.

[0006] Furthermore, the small-particle FePO4 / GO and large-particle FePO4 / GO are both ferric phosphate loaded by precipitation on graphene oxide, and FePO4 / SWCNT is ferric phosphate loaded by precipitation on single-walled carbon nanotubes; The particle size of the small-particle FePO4 / GO is 100-200 nm, and the particle size of the large-particle FePO4 / GO is 3-5 μm.

[0007] Furthermore, the preparation steps of the small-particle FePO4 / GO are as follows: After the ferrous sulfate solution and the graphene oxide dispersion are mixed, a phosphoric acid solution is added at a molar ratio of iron to phosphorus of 1:1.05-1.08, and at 40-50° C., a 20-30wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5-0.6:1, and the oxidation reaction is stirred for 1-2h, and 20-30wt% ammonia water is added dropwise to adjust the pH to 1.5-2.0, and the dropping time is 10-20min, and the small-sized FePO4 / GO is obtained by filtering, washing, and drying; The preparation steps of the large-particle FePO4 / GO are as follows: After the ferrous sulfate solution and the graphene oxide dispersion are mixed, a phosphoric acid solution is added at a molar ratio of iron to phosphorus of 1:1.05-1.08, and at 40-50°C, a 20-30wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5-0.6:1, and the oxidation reaction is stirred for 1-2h, and 20-30wt% ammonia water is added dropwise to adjust the pH to 1.5-2.0, and the dropping time is 50-60min. The large-particle FePO4 / GO is obtained by filtering, washing, and drying.

[0008] The phosphoric acid inserted between the graphene oxide sheets weakens the interaction between the sheets, avoids the reduction of reaction sites caused by particle agglomeration, and improves the reaction activity. The phosphoric acid molecule has a strong polarity. After being introduced into GO, it will form hydrogen bonds with oxygen-containing functional groups (such as carboxyl, hydroxyl, etc.) on the surface of GO. This hydrogen bonding can reduce the van der Waals force and π-π stacking effect between GO sheets, thereby weakening the mutual attraction between sheets. The phosphoric acid molecules are inserted into the interlayer of GO, increasing the distance between the layers, thereby reducing the stacking density between the sheets, making it easier for iron phosphate to be loaded between the layers.

[0009] The large-particle FePO4 / GO is formed by prolonging the ammonia water addition time, so that the newly formed particles are attached to the initially formed particles, and the secondary growth is achieved. The particle size gradually increases, and the primary particles agglomerate to form secondary particles.

[0010] In the preparation of lithium iron phosphate of the present invention, iron phosphate is first loaded on graphene, and the high specific surface area of ​​graphene is used to achieve uniform dispersion of iron phosphate on the surface and between layers of graphene, effectively reducing the agglomeration of iron phosphate particles, controlling the particle size of iron phosphate, and accurately obtaining small-size FePO4 / GO and large-size FePO4 / GO by controlling the pH adjustment time. The loaded material is then pre-calcined with a lithium source to react and grow to form graphene-coated lithium iron phosphate, and finally dopamine is oxidized and self-polymerized to form polydopamine, which is coated on the outer layer of the graphene-coated lithium iron phosphate. After calcination and carbonization, a double-layer coating of porous carbon material and graphene is formed, and the conductivity of the positive electrode material is significantly improved.

[0011] Furthermore, the concentration of the ferrous sulfate solution is 1-2 mol / L, the concentration of the graphene oxide dispersion is 4-5 g / L, and the mass ratio of ferrous sulfate to graphene oxide in the ferrous sulfate solution and the graphene oxide dispersion is 100:3-4.

[0012] Furthermore, the preparation steps of the FePO4 / SWCNT are as follows: After the ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed, a phosphoric acid solution is added at a molar ratio of iron to phosphorus of 1:1.05-1.08, and a 20-30wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5-0.6:1 at 40-50°C. The oxidation reaction is stirred for 1-2h, and 20-30wt% ammonia water is added dropwise to adjust the pH to 1.5-2.0. The dropping time is 10-20min, and the FePO4 / SWCNT is filtered, washed, and dried to obtain the FePO4 / SWCNT.

[0013] Single-walled carbon nanotubes are a type of graphene material, made of a single layer of graphene. Single-walled carbon nanotubes load iron phosphate to promote the dispersion of iron phosphate. Its high aspect ratio structure can be used to build a three-dimensional nanostructure when mixed with graphene-loaded iron phosphate materials for calcination, preventing the agglomeration of graphene-coated materials and optimizing the particle size distribution of the positive electrode material.

[0014] Furthermore, the single-walled carbon nanotube has a length of 1-2 μm and a diameter of 1-2 nm.

[0015] Furthermore, the concentration of the ferrous sulfate solution is 1-2 mol / L, the concentration of the single-walled carbon nanotube dispersion is 1-2 g / L, and the mass ratio of the ferrous sulfate solution to the single-walled carbon nanotube dispersion is 100:3-4.

[0016] Furthermore, the lithium source is one of lithium carbonate and lithium hydroxide.

[0017] Furthermore, the mixed material and the lithium source in the suspension are mixed at a molar ratio of iron to lithium of 1:1-1.02, and the mass proportion of water in the suspension is 50-60%.

[0018] Furthermore, the mass ratio of dopamine hydrochloride to the precursor is 2-5:100; The ammonia water is used to adjust the pH of the reaction system to 8.2-8.5.

[0019] The present invention also provides a graphene-coated lithium iron phosphate positive electrode material, which is prepared by the preparation method described above.

[0020] Beneficial effects of the present invention: (1) In the present invention, the cathode material is prepared by mixing small-sized FePO4 / GO, large-sized FePO4 / GO and FePO4 / SWCNT. The small-sized particles can effectively fill the gaps between the large-sized particles, thereby reducing the porosity of the material. The interlaced combination of FePO4 / SWCNT cylinders and spherical or quasi-spherical FePO4 / GO materials can form a continuous and dense cathode material by filling each other, giving the cathode material a high compaction density.

[0021] (2) The present invention uses carbon nanotubes and graphene to precipitate and load iron phosphate, which can promote the dispersion of iron phosphate particles, avoid excessive particle size caused by agglomeration, and reduce the initial nucleation particles by extending the pH adjustment time, inducing the formation of secondary particles, forming small FePO4 / GO and large FePO4 / GO particles of different particle sizes, and then reacting with the lithium source to generate lithium iron phosphate materials of different particle sizes, thereby optimizing the particle size distribution of the positive electrode material. In addition, carbon nanotubes and graphene will form a coating on the lithium iron phosphate during the subsequent calcination process to improve its conductivity.

[0022] (3) The present invention mixes a precursor and dopamine, and forms a polydopamine coating on the surface of the precursor material through dopamine oxidation self-polymerization. After calcination, carbonization forms an outer coating carbon material, forming a double-layer coating on the positive electrode material to prevent the active components from being exposed to the electrolyte. The porous amorphous carbon layer after calcination of polydopamine can serve as a buffer layer, reducing the volume expansion or shedding of graphene during the charge and discharge process, thereby improving the cycle stability of the material. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 Preparation of small-sized FePO4 / GO particles: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to the deionized water, and ultrasonic dispersion was performed for 2 h to obtain a graphene oxide dispersion. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h, and 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 10 min. The small-sized FePO4 / GO was obtained by filtration, washing and drying. The particle size was 100-150 nm.

[0025] Preparation of large-size FePO4 / GO: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to deionized water. The graphene oxide dispersion was obtained by ultrasonic dispersion treatment for 2 h. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h. 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 50 min. The large-particle FePO4 / GO was obtained by filtration, washing and drying. The particle size was 3-4 μm.

[0026] Preparation of FePO4 / SWCNT: Weigh ferrous sulfate heptahydrate (FeSO4·7H2O) and dissolve it in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Weigh single-walled carbon nanotubes (length 1-2 μm, diameter 1-2 nm) and add them into deionized water. Ultrasonic dispersion treatment is performed for 2 h to obtain a single-walled carbon nanotube dispersion. The concentration of the single-walled carbon nanotube dispersion is 2 g / L. The ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed at a mass ratio of ferrous sulfate to single-walled carbon nanotubes of 100:3. After mixing, a phosphoric acid solution (concentration 85 wt%) is added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature is controlled at 40°C by heating in a water bath. 30 wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction is stirred for 2 h. 20 wt% ammonia water is added dropwise to adjust the pH to 1.7. The dropping time is 10 min. The FePO4 / SWCNT is filtered, washed, and dried.

[0027] Preparation of positive electrode materials: Step 1: small-sized FePO4 / GO, large-sized FePO4 / GO and FePO4 / SWCNT are mixed in a mass ratio of 3:2:1 to form a mixture; Step 2, lithium carbonate is added to the mixture, and the amount of lithium carbonate added is calculated according to the mass of iron element added during the preparation of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT. Lithium carbonate is added and mixed at a molar ratio of iron to lithium of 1:1, and then deionized water is added to form a suspension, in which the mass proportion of water in the suspension is 60%. A solid material is obtained after spray drying, and pre-calcined at 700°C for 8h in a nitrogen atmosphere to form a precursor; Step 3. Add the precursor into deionized water at a mass concentration of 1 g / L, ultrasonically disperse for 2 hours, add dopamine hydrochloride at a mass ratio of 5:100 to the precursor, and add ammonia water to adjust the pH to 8.5. Heat in a water bath to control the temperature at 40°C, stir the reaction for 6 hours, filter and vacuum dry, and calcine at 700°C for 4 hours under a nitrogen atmosphere to obtain the positive electrode material.

[0028] Example 2 The difference from Example 1 is that the mass ratio of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT is adjusted to 5:2:1, and the other conditions and steps are the same as Example 1.

[0029] Example 3 The difference from Example 1 is that the mass ratio of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT is adjusted to 4:1.5:0.75, and the other conditions and steps are the same as Example 1.

[0030] Example 4 The difference from Example 3 is that, in the process of preparing small-particle FePO4 / GO and large-particle FePO4 / GO, the ferrous sulfate solution and the graphene oxide dispersion are mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3.5, and in the process of preparing FePO4 / SWCNT, the ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed at a mass ratio of ferrous sulfate to single-walled carbon nanotubes of 100:3.5. Other conditions and steps are the same as Example 3.

[0031] Example 5 The difference from Example 3 is that, in the process of preparing small-particle FePO4 / GO and large-particle FePO4 / GO, the ferrous sulfate solution and the graphene oxide dispersion are mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:4, and in the process of preparing FePO4 / SWCNT, the ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed at a mass ratio of ferrous sulfate to single-walled carbon nanotubes of 100:4. Other conditions and steps are the same as Example 3.

[0032] Example 6 The difference from Example 3 is that the mass ratio of dopamine hydrochloride to the precursor is adjusted from 5:100 to 3:100. The specific steps are as follows: Preparation of small-sized FePO4 / GO particles: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to the deionized water, and ultrasonic dispersion was performed for 2 h to obtain a graphene oxide dispersion. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h, and 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 10 min. The small-sized FePO4 / GO was obtained by filtration, washing and drying. The particle size was 100-150 nm.

[0033] Preparation of large-size FePO4 / GO: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to deionized water. The graphene oxide dispersion was obtained by ultrasonic dispersion treatment for 2 h. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h. 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 50 min. The large-particle FePO4 / GO was obtained by filtration, washing and drying. The particle size was 3-4 μm.

[0034] Preparation of FePO4 / SWCNT: Weigh ferrous sulfate heptahydrate (FeSO4·7H2O) and dissolve it in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Weigh single-walled carbon nanotubes (length 1-2 μm, diameter 1-2 nm) and add them into deionized water. Ultrasonic dispersion treatment is performed for 2 h to obtain a single-walled carbon nanotube dispersion. The concentration of the single-walled carbon nanotube dispersion is 2 g / L. The ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed at a mass ratio of ferrous sulfate to single-walled carbon nanotubes of 100:3. After mixing, a phosphoric acid solution (concentration 85 wt%) is added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature is controlled at 40°C by heating in a water bath. 30 wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction is stirred for 2 h. 20 wt% ammonia water is added dropwise to adjust the pH to 1.7. The dropping time is 10 min. The FePO4 / SWCNT is filtered, washed, and dried.

[0035] Preparation of positive electrode materials: Step 1: small-sized FePO4 / GO, large-sized FePO4 / GO and FePO4 / SWCNT are mixed in a mass ratio of 4:1.5:0.75 to form a mixture; Step 2, lithium carbonate is added to the mixture, and the amount of lithium carbonate added is calculated according to the mass of iron element added during the preparation of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT. Lithium carbonate is added and mixed at a molar ratio of iron to lithium of 1:1, and then deionized water is added to form a suspension, in which the mass proportion of water in the suspension is 60%. A solid material is obtained after spray drying, and pre-calcined at 700°C for 8h in a nitrogen atmosphere to form a precursor; Step 3. Add the precursor into deionized water at a mass concentration of 1 g / L, ultrasonically disperse for 2 hours, add dopamine hydrochloride at a mass ratio of 3:100 to the precursor, and add ammonia water to adjust the pH to 8.5. Heat in a water bath to control the temperature at 40°C, stir the reaction for 6 hours, filter and vacuum dry, and calcine at 700°C for 3 hours in a nitrogen atmosphere to obtain the positive electrode material.

[0036] Example 7 The difference from Example 3 is that the mass ratio of dopamine hydrochloride to the precursor is adjusted from 5:100 to 2:100. The specific steps are as follows: Preparation of small-sized FePO4 / GO particles: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to the deionized water, and ultrasonic dispersion was performed for 2 h to obtain a graphene oxide dispersion. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h, and 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 10 min. The small-sized FePO4 / GO was obtained by filtration, washing and drying. The particle size was 100-150 nm.

[0037] Preparation of large-size FePO4 / GO: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to deionized water. The graphene oxide dispersion was obtained by ultrasonic dispersion treatment for 2 h. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h. 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 50 min. The large-particle FePO4 / GO was obtained by filtration, washing and drying. The particle size was 3-4 μm.

[0038] Preparation of FePO4 / SWCNT: Weigh ferrous sulfate heptahydrate (FeSO4·7H2O) and dissolve it in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Weigh single-walled carbon nanotubes (length 1-2 μm, diameter 1-2 nm) and add them into deionized water. Ultrasonic dispersion treatment is performed for 2 h to obtain a single-walled carbon nanotube dispersion. The concentration of the single-walled carbon nanotube dispersion is 2 g / L. The ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed at a mass ratio of ferrous sulfate to single-walled carbon nanotubes of 100:3. After mixing, a phosphoric acid solution (concentration 85 wt%) is added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature is controlled at 40°C by heating in a water bath. 30 wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction is stirred for 2 h. 20 wt% ammonia water is added dropwise to adjust the pH to 1.7. The dropping time is 10 min. The FePO4 / SWCNT is filtered, washed, and dried.

[0039] Preparation of positive electrode materials: Step 1: small-sized FePO4 / GO, large-sized FePO4 / GO and FePO4 / SWCNT are mixed in a mass ratio of 4:1.5:0.75 to form a mixture; Step 2, lithium carbonate is added to the mixture, and the amount of lithium carbonate added is calculated according to the mass of iron element added during the preparation of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT. Lithium carbonate is added and mixed at a molar ratio of iron to lithium of 1:1, and then deionized water is added to form a suspension, in which the mass proportion of water in the suspension is 60%. A solid material is obtained after spray drying, and pre-calcined at 700°C for 8h in a nitrogen atmosphere to form a precursor; Step 3. Add the precursor into deionized water at a mass concentration of 1 g / L, ultrasonically disperse for 2 hours, add dopamine hydrochloride at a mass ratio of dopamine hydrochloride to the precursor of 2:100, and add ammonia water to adjust the pH to 8.5. Heat in a water bath to control the temperature at 40°C, stir the reaction for 6 hours, filter and vacuum dry, and calcine at 700°C for 2 hours under a nitrogen atmosphere to obtain the positive electrode material.

[0040] Comparative Example 1 Compared with Example 1, FePO4 / SWCNT is not added when preparing the mixture in this comparative example, and the specific steps are as follows: Preparation of small-sized FePO4 / GO particles: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to the deionized water, and ultrasonic dispersion was performed for 2 h to obtain a graphene oxide dispersion. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h, and 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 10 min. The small-sized FePO4 / GO was obtained by filtration, washing and drying. The particle size was 100-150 nm.

[0041] Preparation of large-size FePO4 / GO: Ferrous sulfate heptahydrate (FeSO4·7H2O) was weighed and dissolved in deionized water to form a ferrous sulfate solution with a concentration of 1 mol / L. Graphene oxide was weighed and added to deionized water. The graphene oxide dispersion was obtained by ultrasonic dispersion treatment for 2 h. The concentration of the graphene oxide dispersion was 5 g / L. The ferrous sulfate solution and the graphene oxide dispersion were mixed at a mass ratio of ferrous sulfate to graphene oxide of 100:3. After mixing, a phosphoric acid solution (with a concentration of 85 wt%) was added thereto at a molar ratio of iron to phosphorus of 1:1.05. The temperature was controlled at 40°C by heating in a water bath. A 30 wt% H2O2 solution was added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5:1. The oxidation reaction was stirred for 2 h. 20 wt% ammonia water was added dropwise to adjust the pH to 1.7. The dropping time was 50 min. The large-particle FePO4 / GO was obtained by filtration, washing and drying. The particle size was 3-4 μm.

[0042] Preparation of positive electrode materials: Step 1: Mix small-sized FePO4 / GO and large-sized FePO4 / GO in a mass ratio of 3:2 to form a mixture; Step 2: Add lithium carbonate to the mixture. The amount of lithium carbonate added is calculated according to the mass of iron added during the preparation of small-particle FePO4 / GO and large-particle FePO4 / GO. Lithium carbonate is added and mixed at a molar ratio of iron to lithium of 1:1. Deionized water is then added to form a suspension. The mass proportion of water in the suspension is 60%. A solid material is obtained after spray drying. The solid material is pre-calcined at 700°C for 8 hours in a nitrogen atmosphere to form a precursor. Step 3. Add the precursor into deionized water at a mass concentration of 1 g / L, ultrasonically disperse for 2 hours, add dopamine hydrochloride at a mass ratio of 5:100 to the precursor, and add ammonia water to adjust the pH to 8.5. Heat in a water bath to control the temperature at 40°C, stir the reaction for 6 hours, filter and vacuum dry, and calcine at 700°C for 4 hours under a nitrogen atmosphere to obtain the positive electrode material.

[0043] Comparative Example 2 Compared with Example 1, dopamine hydrochloride was not added for secondary carbon coating when preparing the positive electrode material in this comparative example. Other conditions and steps were the same as those in Example 1. The specific steps for preparing the positive electrode material were as follows: Step 1: small-sized FePO4 / GO, large-sized FePO4 / GO and FePO4 / SWCNT are mixed in a mass ratio of 3:2:1 to form a mixture; Step 2: Add lithium carbonate to the mixture. The amount of lithium carbonate added is calculated according to the mass of iron added during the preparation of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT. Lithium carbonate is added and mixed at a molar ratio of iron to lithium of 1:1. Deionized water is then added to form a suspension, in which the mass proportion of water in the suspension is 60%. A solid material is obtained after spray drying, and the positive electrode material is calcined at 750°C for 10 hours under a nitrogen atmosphere.

[0044] Comparative Example 3 Compared with Example 1, in this comparative example, the mixed material, the lithium source and the polydopamine are directly mixed and calcined to prepare the positive electrode material. The specific preparation steps are as follows: Step 1: small-sized FePO4 / GO, large-sized FePO4 / GO and FePO4 / SWCNT are mixed in a mass ratio of 3:2:1 to form a mixture; Step 2, lithium carbonate is added to the mixture. The amount of lithium carbonate added is calculated according to the mass of iron added during the preparation of small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT. Lithium carbonate is added and mixed at a molar ratio of iron to lithium of 1:1, and then polydopamine is added. The mass ratio of polydopamine to the total of the mixture and lithium carbonate is 5:100. Deionized water is added to form a suspension, and the mass ratio of water in the suspension is 60%. A solid material is obtained after spray drying, and the solid material is calcined at 750°C for 10 hours in a nitrogen atmosphere to form a positive electrode material.

[0045] Compaction test and application test were performed on the positive electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3: lithium iron phosphate positive electrode material, PVDF, and carbon black were weighed in a mass ratio of 90:6:4, and then dispersed by adding an appropriate amount of NMP solvent, uniformly coated on aluminum foil, dried in an oven at 100°C for 8 hours, rolled and cut into circular pole pieces, weighed and measured for thickness, and the pole piece compaction density was calculated; the pole pieces were assembled into CR2430 button lithium ion batteries, and electrochemical performance tests were performed. The test results are shown in Table 1.

[0046]

[0047] As can be seen from Table 1, in Examples 1 to 3 of the present invention, by adjusting the mixing ratio of iron phosphate materials of different particle sizes and shapes, the particle distribution of lithium iron phosphate positive electrode materials is optimized, the pores between particles are reduced, and the compaction density of the material is effectively improved, and its discharge specific capacity is relatively high, and the cycle capacity retention rate can reach 90% at a rate of 1C. When the amount of graphene coating increases in Examples 4 and 5, ion transmission will be hindered, resulting in a decrease in discharge specific capacity and a slight decrease in cycle performance. For the secondary coating of polydopamine, Examples 6 and 7, based on Example 3, reduce the amount of dopamine hydrochloride added during the preparation process and reduce the coating thickness. The electrochemical performance of the positive electrode material in Example 6 is significantly improved, and the positive electrode material in Example 7 has a reduced cycle performance due to insufficient secondary coating thickness. Without adding FePO4 / SWCNT, the positive electrode material prepared in Comparative Example 1 has a loose distribution structure between particles compared with Example 1, and the compaction density index is lower, and the electrochemical performance is not as good as Example 1; in Comparative Example 2, no secondary coating is performed, the cycle performance is poor, and the capacity retention rate is lower than 85%; in Comparative Example 3, the positive electrode material is directly mixed and calcined to prepare, and polydopamine cannot be evenly coated on the surface of the precursor, and the surface of the secondary coating layer formed is uneven, which will cause the coating layer to crack or fall off during the cycle, and the cycle performance is significantly reduced.

[0048] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a graphene-coated lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1, mixing small-particle FePO4 / GO, large-particle FePO4 / GO and FePO4 / SWCNT in a mass ratio of (3-5): (1-2): (0.5-1) to form a mixture; Step 2: adding lithium source and water to the mixture to form a suspension, spray drying to obtain a solid material, and pre-calcining at 700-750° C. for 6-8 hours under a nitrogen atmosphere to form a precursor; Step 3: The precursor is dispersed in water at a mass concentration of 1-3 g / L, dopamine hydrochloride and ammonia water are added, reacted at 30-40° C. for 6-8 hours, filtered and vacuum dried, and calcined at 700-750° C. for 2-4 hours under a nitrogen atmosphere to obtain a positive electrode material; The particle size of the small-particle FePO4 / GO is 100-150 nm, and the particle size of the large-particle FePO4 / GO is 3-4 μm.

2. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The small-particle FePO4 / GO and large-particle FePO4 / GO are both ferric phosphate loaded by precipitation on graphene oxide, and FePO4 / SWCNT is ferric phosphate loaded by precipitation on single-walled carbon nanotubes.

3. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The preparation steps of the small-particle FePO4 / GO are as follows: After the ferrous sulfate solution and the graphene oxide dispersion are mixed, a phosphoric acid solution is added at a molar ratio of iron to phosphorus of 1:1.05-1.08, and at 40-50° C., a 20-30wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5-0.6:1, and the oxidation reaction is stirred for 1-2h, and 20-30wt% ammonia water is added dropwise to adjust the pH to 1.5-2.0, and the dropping time is 10-20min, and the small-sized FePO4 / GO is obtained by filtering, washing, and drying; The preparation steps of the large-particle FePO4 / GO are as follows: After the ferrous sulfate solution and the graphene oxide dispersion are mixed, a phosphoric acid solution is added at a molar ratio of iron to phosphorus of 1:1.05-1.08, and at 40-50°C, a 20-30wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5-0.6:1, and the oxidation reaction is stirred for 1-2h, and 20-30wt% ammonia water is added dropwise to adjust the pH to 1.5-2.0, and the dropping time is 50-60min. The large-particle FePO4 / GO is obtained by filtering, washing, and drying.

4. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 3, characterized in that: The concentration of the ferrous sulfate solution is 1-2 mol / L, the concentration of the graphene oxide dispersion is 4-5 g / L, and the mass ratio of the ferrous sulfate solution to the graphene oxide dispersion is 100:3-4.

5. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The preparation steps of the FePO4 / SWCNT are as follows: After the ferrous sulfate solution and the single-walled carbon nanotube dispersion are mixed, a phosphoric acid solution is added at a molar ratio of iron to phosphorus of 1:1.05-1.08, and a 20-30wt% H2O2 solution is added dropwise at a molar ratio of H2O2 to divalent iron ions of 0.5-0.6:1 at 40-50°C. The oxidation reaction is stirred for 1-2h, and 20-30wt% ammonia water is added dropwise to adjust the pH to 1.5-2.

0. The dropping time is 10-20min, and the FePO4 / SWCNT is filtered, washed, and dried to obtain the FePO4 / SWCNT.

6. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 5, characterized in that: The single-walled carbon nanotube has a length of 1-2 μm and a diameter of 1-2 nm.

7. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 5, characterized in that: The concentration of the ferrous sulfate solution is 1-2 mol / L, the concentration of the single-walled carbon nanotube dispersion is 1-2 g / L, and the mass ratio of the ferrous sulfate solution to the single-walled carbon nanotube dispersion is 100:3-4.

8. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mixed material and the lithium source in the suspension are mixed at a molar ratio of iron to lithium of 1:1-1.02, and the mass proportion of water in the suspension is 50-60%.

9. The method for preparing a graphene-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of dopamine hydrochloride to the precursor is 2-5:100; The ammonia water is used to adjust the pH of the reaction system to 8.2-8.

5.

10. A graphene-coated lithium iron phosphate positive electrode material, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Cathode material of lithium ion phosphate battery

    CN105047918A

  • Preparation method for cathode material of lithium iron phosphate battery

    CN105098152A

  • Lithium-free anode material for secondary battery manufacturing and manufacturing method of lithium-free anode material

    CN106099104A

  • Device for preparing graphene carbon nanotube modified positive electrode material and preparation method

    CN108281661A

  • Preparation method of composite anode material of lithium ion battery

    CN108321361A